An assessment of the Arabic language programme for Human Sciences students at International Islamic University Malaysia - Mohammad Lotfie, Maskanah; Zubir, Badri Najib; Md Ghalib, Mohd. Feham (2012)
This study focuses on the teaching and learning of Arabic for Human Sciences (HS) undergraduates at International Islamic University Malaysia (IIUM). Even though English is the medium of instruction for the majority of IIUM academic programmes, Arabic has been incorporated into the curricula of Communication, English Language and Literature, History and Civilization, Political Science, Psychology and Sociology and Anthropology programmes. The incorporation of the language is a measure to effectively realize the University’s philosophy in augmenting Islamic perspective and values into contemporary and conventional curriculum. However, there is a need to evaluate the Arabic courses for HS students after having been implemented since 2001. The study investigates the nature in which Arabic is taught to students who essentially speak Malay as their mother tongue and English as a second language. The main objectives of the study are to investigate academics’ and students’ perceptions of the current courses; to test students’ retention of the language upon completing the final course; and to test the effects of selected instructional interventions in improving Arabic language learning. The study is extensive and adopts a mixed methods approach where it included surveys, a retention study and a quasi-experiment. Data collection involved a total of 355 students and 19 academics. The first phase of the study evaluated the current practice while the second compared Information and Communications Technology-based approach (ICT), Problem-Based Learning (PBL) and conventional language teaching. Arabic is believed to be an important vehicle in achieving institutional vision and mission. While the practice of learning the language will continue, the pedagogical concerns in acquiring the language merit systematic attention. The findings of the study are crucial in determining the future direction of the Arabic courses for HS students.